Професійна підготовка соціальних працівників: досвід Скандинавських країн - Кравченко, Оксана; Kravchenko, O. (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті висвітлено зміст професійної підготовки соціальних працівників у Скандинавських країнах із виокремленням загальних рекомендацій для вітчизняної соціальної освіти. Встановлено, що важливим аспектом вищої освіти Швеції, Нідерландів, Фінляндії є принцип «академічної свободи», який має 4 статуси: свобода університету у визначенні змісту навчальних планів та освітніх програм; свобода факультету із визначення змісту дисциплін; свобода викладача із визначення змісту свого курсу; свобода студента у виборі дисциплін і спеціалізації. On the basis of studying the experience of the Nordic countries in the training of social workers singled out general recommendations for possible implementation feasibility of domestic social education: college or establishment of the National Council on Social Work to coordinate the development of curricula in accordance with educational standards and educational programs; the need for reasonable differentiation of training for independent scientific work in academic and professional research institutions and professional practitioners to work on a particular specialty; wider implementation of integrative interdisciplinary character and links with training in social work; research into the proceedings of innovative, creative individual and group learning; review approaches to practice toward the distribution of workload, continuity and forms of protection and reporting; research into the implementation of supervisors from among professionals from institutions of social practice students - future social workers; the shift from classroom to independent work, increased attention to individual written work; Development of an effective system of training teachers.
Training of social workers: the experience of the Nordic countries
Keywords: освіта; соціальний працівник; стандарт вищої освіти; навчання; education; social worker; higher education and training